EVALUATION OF AETIOLOGY AND EFFICACY OF MANAGEMENT PROTOCOL OF EPISTAXIS - Hussain, Gulshan; Iqbal, Mahid; Shah, Shahid Ali; Said, Mohammad; ullah, Sana; Khan, Sharafat Ali; Iqbal, Muhammad; Zaman, Javed (Journal of Ayub Medical College Abbottabad, 2006)
Background: Epistaxis is one of the commonest medical emergencies. It affects all age groups and both sexes. The cause may be local or systemic but in majority it is spontaneous and idiopathic. Trauma is considered to be a major aetiological factor. Various treatment protocols are utilized to control epistaxis derpending upon the type, severity and cause of bleeding. Methods: This descriptive study was designed to evaluate the aetiology and efficacy of management protocol of epistaxis in a tertiary care setting. 313 patients underwent prospective evaluation by consultant and non-consultant doctors with considerable experience in Ear, Nose & Throat (ENT) emergencies management. Standard principles were followed in the management. Results: This study demonstrated a bimodal distribution with incidence peaks in below 25 years & above 50 years of age. Males were affected twice more than the females (2.15:1.04). Anterior nasal bleeding was noted in majority of the patients. Anterior nasal packing was the most effective method of controlling anterior epistaxis. While posterior bleeding was controlled by posterior nasal packing with Foley's catheter. The most common cause was found to be trauma, followed by hypertension. Conclusion: It may be concluded from this study that epistaxis is the m ost common ENT emergency, affecting all age groups. It has a bimodal age presentation and affects males twice more than females. Anterior bleeding is more common than posterior bleeding. Epistaxis may be controlled with chemical/electro-cautery if the bleeding point is visible. In case of failure to localize or access a bleeding point or profuse bleeding, anterior nasal packing can effectively control majority of epistaxis. Foley's catheter is a good option that can be used for posterior nasal packing. Gelfoam may be used for controlling epistaxis in cases of bleeding disorders, when there is mucosal ooze. Key words: Epistaxis, Nasal packing, Foley's catheter.